Influence of Commitment, Reward, and Punishment on Em-ployees Performance at DAMRI Lampung - Muhamad Yusrizal; Nova Mardiana (International Forum of Researchers and Lecturers, 2025)
This study explores the impact of organizational commitment, rewards, and punishment on employee performance at Perum DAMRI Bandar Lampung, a branch of the state-owned enterprise specializing in land transportation services for passengers and cargo. The research arises from the necessity to improve employee performance by leveraging both internal and external motivational factors, including employee loyalty, reward systems, and disciplinary actions. Using a quantitative research design, data were collected through a structured survey distributed to 168 active employees of the organization. The collected data were then analyzed using multiple linear regression through SPSS version 24. The study found that organizational commitment and rewards have a significant and positive influence on employee performance. These findings support the proposed hypotheses and highlight the importance of fostering employee loyalty and implementing an effective reward system to boost performance outcomes. In contrast, the analysis revealed that punishment does not have a significant positive effect on employee performance. This suggests that punitive measures alone may not be effective in encouraging desired work behaviors or improving overall performance. Based on these findings, it is recommended that Perum DAMRI Bandar Lampung prioritize initiatives that strengthen organizational commitment and develop a fair, transparent, and performance-based reward system. Such efforts are likely to enhance employee motivation and productivity. Additionally, the current approach to punishment should be critically evaluated to determine its role and effectiveness in supporting performance goals. A more constructive disciplinary framework may be needed to align with modern human resource management practices. This study contributes to the broader understanding of performance management in state-owned enterprises, especially in the transportation sector.